2014
DOI: 10.30970/cma7.0268
|View full text |Cite
|
Sign up to set email alerts
|

New ternary phases from the R–Au–Ga systems (R = Gd-Tm)

Abstract: Twenty rare-earth gold gallides, RAu 3 Ga 7 (ScRh 3 Si 7-type, space group R-3c, Z = 6, hR66), RAu 3±x Ga 3±x (YCd 6-type, space group Im-3, Z = 24, cI68), RAu 1+x Ga 2-x (MgCuAl 2-type, space group Cmcm, Z = 4, oS16) (R = Gd-Tm) and R 14 Au 34+x Ga 17-x (Gd 14 Ag 51-type, space group P6/m, Z = 1, hP65) (R = Er, Tm), were synthesized by arc-melting, followed by annealing at 400-600ºC. Six phases RAu 1+x Ga 3-x (BaAl 4-type, space group I4/mmm, Z = 2, tI10) (R = Gd) and R 3 Au 3+x Ga 8-x (La 3 Al 11-type, space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Due to the differences in the respective bonding situations, however, these compounds have to be considered isopointal rather than isotypic. For these 1‐1‐2 representatives the gallides ( MT Ga 2 ; M =Ca, Sc, Y, Gd–Lu; T =Ni, Pd, Pt, Au), the indides ( MT In 2 ; M =Na, Ca–Ba, Y, La–Nd, Eu–Dy, Yb; T =Ru, Rh, Ir, Ni, Pd, Pt, Cu, Au and Eu 1− x Sr x PtIn 2 ), the thallides ( MT Tl 2 ; M =Sr, Eu; T =Pd, Pt), the silicide ScPt 2 Si, the stannides MT Sn 2 ( M =Ca, Eu, Yb; T =Rh, Ir, Pd) and the phosphide PdNi 2 P have been reported. For aluminum finally, the representatives MT Al 2 ( M =Sc, Y, La–Nd, Sm, Gd–Lu; T =Co, Ni, Cu, Pd, Pt) have been prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the differences in the respective bonding situations, however, these compounds have to be considered isopointal rather than isotypic. For these 1‐1‐2 representatives the gallides ( MT Ga 2 ; M =Ca, Sc, Y, Gd–Lu; T =Ni, Pd, Pt, Au), the indides ( MT In 2 ; M =Na, Ca–Ba, Y, La–Nd, Eu–Dy, Yb; T =Ru, Rh, Ir, Ni, Pd, Pt, Cu, Au and Eu 1− x Sr x PtIn 2 ), the thallides ( MT Tl 2 ; M =Sr, Eu; T =Pd, Pt), the silicide ScPt 2 Si, the stannides MT Sn 2 ( M =Ca, Eu, Yb; T =Rh, Ir, Pd) and the phosphide PdNi 2 P have been reported. For aluminum finally, the representatives MT Al 2 ( M =Sc, Y, La–Nd, Sm, Gd–Lu; T =Co, Ni, Cu, Pd, Pt) have been prepared.…”
Section: Introductionmentioning
confidence: 99%
“…CeIr 3 Ge 7 crystallizes in the R 3c rhombohedral ScRh 3 Si 7 structure type 25,26 . The very few 1-3-7 compounds known so far are RAu 3 Ga 7 (R = Gd-Yb) 27,28 , non-magnetic RAu 3 Al 7 (R = Ce-Sm, Gd-Lu) 29 , and magnetic Eu(Rh,Ir) 3 Ge 7 30 . Recently we discovered the first magnetic Ce and Yb 1-3-7 compounds.…”
mentioning
confidence: 99%
“…Representatives of R 14 (Au, M) 51 compounds comprise R = Y, La−Nd, Sm−Tb, Ho, Er, Yb, Lu; M = Al, Ga, Ge, In, Sn, Sb, Bi, including Yb 14 (Au, Sn) 51 , and Lu 14 (Au, Ga) 51 which are ternary representatives with no reported binary phase, as well as a replication of the recently reported Er 14 (Au, Ga) 51 ternary representative for comparison. 48 The details of the crystallographic investigation along with the positional data for three example compounds (Gd 14 (Au, Sb) 51 , Lu 14 (Au, Ga) 51 , and La 14 (Au, Bi) 51 ) are summarized in Tables 1 and 2. (See Appendix for CCDC numbers of all samples.)…”
Section: Resultsmentioning
confidence: 99%
“…The literature appears inconsistent with its allowance of mixing at this disordered atomic site. In the work previously mentioned by Verbovytskyy, mixing was determined by powder X-ray diffraction to exist at all seven sites, including the disordered Au7, 48 while in recent works by Belgacem et al and Lin and Corbett mixing at this site is discounted. 50 A disordered Er site in the Er 14 Cu 51-x Ga x (5.5 ≤ x ≤ 11.0) compound reported by Belgacem et al that is near the Au7 site would have likely shown preferential occupancy if the Au7 site showed mixing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation